Cinemas and cinemagoing in wartime Britain, 1939-45 : the utility dream palace - Farmer, Richard (Studies in popular culture., 2016)
During the Second World War, the popularity and importance of the cinema in Britain was at its peak. Richard Farmer provides a social and cultural history of cinemas and cinemagoing in Britain between 1939 and 1945, and explores the impact that the war had on the places in which British people watched films.